A study on awareness of organizational citizenship behaviour (OCB) among academicians in Kolej Poly Tech MARA (KPTM), Kuantan / Nurul Ain Mohamed @ Abd Aziz - Mohamed @ Abd Aziz, Nurul Ain (2013)
Organizational Citizenship Behaviour (OCB) is the actions taken by employees that are beyond their work scope and what are expected by the organization. In Malaysia, OCB concept is still lack of exposure in the organization especially in the private college sector. It is a reason why they do not know and understand about OCB and at the same time not aware about it. Actually, if the organization aware about OCB concept, it can help them to increase their performance and profit. So, a study was conducted to investigate the level of OCB awareness among academicians in Kolej Poly-Tech Mara (KPTM), Kuantan, Pahang. Questionnaire was prepared and a research had been conducted with the academicians of KPTM. The result shows that most of the respondents are aware of OCB. The contributing elements to the level of awareness on OCB among academicians in the workplace are job satisfaction, organizational commitment and job stress. The most contributing elements are job satisfaction and organizational commitment. It is because when academicians are satisfied with their job and organizational commitment so they will become more aware of OCB even when facing job stress. However, it was found that OCB concept is still less embedded in the organization in Malaysia is the main reason why academicians do not know and understand about OCB. Besides that, they never had been exposed with the importance and benefits of OCB itself.